Pyoderma gangrenosum associated with left iliac vein compression syndrome: presentation of difficult diagnosis - Verena Mony Paes de Freitas; Silvia Marcondes Pereira; Mílvia Maria Simões e Silva Enokihara; Silmara da Costa Pereira Cestari (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Pyoderma gangrenosum is a rare neutrophilic dermatosis of unknown etiology, of which the most frequent clinical manifestations are ulcers. The diagnosis difficulty is, among other things, to rule out other causes of ulcers, since it is considered a diagnosis of exclusion. Skin ulcerations may also occur in the iliac vein compression syndrome, which, like pyoderma gangrenosum, mainly affects young women. Because they have such similar characteristics, the presence of vascular disease may hinder the diagnosis of concurrent pyoderma gangrenosum. Because of the clinical relevance of ulcerated lesions and scars, the early diagnosis and treatment of this condition is considered extremely important. We report a case in which the two diseases were associated, hampering the diagnosis of pyoderma gangrenosum.